Red Cell Parameters in Beta Thalassemia Trait; Comparison between Iron Deficient and Non-Deficient Carriers - Nazish Tahir; Saeed Akhtar Khan Khattak; Ghulam Murtaza Shaikh; Zunera Sajjad; Tamoor Bin Hanif; Nighat Jamal (Journal of Bahria University Medical and Dental College)
Objective: To compare hematological parameters in iron-deficient and non-deficient carriers of beta thalassemia trait. Study Design And Setting: Comparative cross-sectional study. This study was conducted at the Department of Hematology at PNS SHIFA Hospital, Karachi for six months (February 2023 to July 2023).